Evaluation of Blended Learning in Biology Subject at State Senior High School 1 in Jambi City, Indonesia - Mico Arisanto; Zulyusri Zulyusri; Lufri Lufri (MO.RI Publishing, 2023)
The aim of this research is to evaluate the implementation of blended learning in the biology subject at State Senior High School 1 in Jambi City, considering various aspects such as context, input, process, and product, as well as analyzing the inhibiting factors of blended learning implementation in the biology subject. This study used a descriptive evaluation research method, utilizing the CIPP evaluation model, and was conducted at State Senior High School 1 in Jambi City. The data was collected through questionnaires and interviews and analyzed both quantitatively and qualitatively. The evaluation results of the context, input, process, and product aspects showed that the implementation of blended learning in the biology subject at State Senior High School 1 in Jambi City has been quite successful and has achieved the objectives of blended learning, which are to accommodate the needs of both students and teachers to achieve all aspects of biology learning competencies. However, inhibiting factors of the blended learning implementation model were identified, including communication technology, such as unstable internet networks, discomfort in interpersonal communication between students and teachers, lack of understanding among students of digital media communication culture, levels of stress and decreased learning motivation, non-conducive learning environment, and low commitment and empathy from teachers.